Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, A.; Mediavilla, S. (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species - Mediavilla, S.; Escudero, A. (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Leaf growth; leaf life span; mean residence time; nitrogen; phosphorus